1993
DOI: 10.1038/clpt.1993.31
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine methyltransferase activity in a sample population of black subjects in Florida

Abstract: Thiopurine methyltransferase (TPMT), is an enzyme detected in the human red blood cell that catalyzes the S-methylation of thiopurine drugs and is known to exist as a genetic polymorphism in white subjects. Investigations in this laboratory of red blood cell TPMT showed interethnic differences also existed in North American black subjects. A sample group of black subjects in Florida had a mean activity of 8.64 +/- 3.47 U/ml red blood cells and an antimode of 6.5 units, which represented values significantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
11
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
7
11
3
Order By: Relevance
“…The percentage of subjects with intermediate RBC TPMT activity in this population sample was similar to what has previously been reported in other studies [14,15,19,22,36] but was different from the high percentage reported in black subjects by Jones et al [20]. Both the probit plot with the inflection point (Fig.…”
Section: Disc U Ssi 0 Nsupporting
confidence: 83%
See 1 more Smart Citation
“…The percentage of subjects with intermediate RBC TPMT activity in this population sample was similar to what has previously been reported in other studies [14,15,19,22,36] but was different from the high percentage reported in black subjects by Jones et al [20]. Both the probit plot with the inflection point (Fig.…”
Section: Disc U Ssi 0 Nsupporting
confidence: 83%
“…We have reported 9.2% higher RBC TPMT activity in male subjects in Norwegian elderly patients on drug therapy [13] [20,22,36]. In a rat study, testosterone induced RBC TPMT activity [37].…”
Section: Disc U Ssi 0 Nmentioning
confidence: 99%
“…A review of literature showed that Caucasians have higher median TPMT activity in erythrocytes than black populations [10,11,21], but North American Caucasians, European Caucasians, and Asian populations (healthy Korean children) [11,21,22] have approximately the same median TPMT activity in erythrocytes. The frequency of TPMT genetic variation in Thai children in the present study is the same as that reported in the Caucasian populations, therefore TPMT genotype in Thai children could reflect TPMT phenotypic activity in erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that tissues derived from males have approximately 10% higher levels of TPMT activity than those from females [19,23,25], but other studies do not find significant sex differences [26][27][28]. Uneven frequency distribu tions of TPMT activity are also found in diverse ethnic groups [26,28].…”
Section: Genetic Polymorphism Of Tpmtmentioning
confidence: 70%